Effect of an educational intervention on nurses' competence in activities of daily living support in end-of-life care using a pretest-posttest repeated measures design - Gattinger Heidrun; Ott Stefan; Maurer Carola; Marty-Teuber Brigitte; Hantikainen Virpi; Fringer Andre (BMC, 2025)
Background Most patients in specialized palliative care units need nursing support to perform activities of daily living (ADL), such as using a toilet or transferring out of a bed or chair. To deliver high-quality ADL support that facilitates patients' movement and protects nurses' musculoskeletal health, nurses need appropriate knowledge and skills. The objective of this study is to investigate the impact of education based on the "Advanced Kinaesthetics in Palliative care (AdKinPal) program" on the competence in Kinaesthetics, self-efficacy regarding ADL support in end-of-life care and musculoskeletal complaints of nurses from specialist palliative care units.
Methods A pretest-posttest repeated measures design was applied. The study took place in three specialised units for palliative care in Switzerland between June 2018 and April 2020. All the nurses who worked in participating wards (n = 62) and fulfilled the inclusion criteria were asked to participate. The intervention - the AdKinPal program - is an education-based training program conducted for six months. We took measurements using self-administered questionnaires at three points before and after the intervention. Using descriptive statistics, repeated measurement analysis of variance (ANOVA) and independent-samples t-tests, we analysed the participants' demographic characteristics as well as developments over time and relationships between the three outcome variables: Kinaesthetics competence, self-efficacy regarding ADL support in end-of-life care and musculoskeletal complaints.
Results Fifty-nine nurses and one physiotherapist participated, and 38 participants (63%) responded to all three questionnaires. The AdKinPal training improved the nurses' perceived Kinaesthetics competence and self-efficacy regarding ADL support in end-of-life care. Participants who reported lower back, neck or shoulder pain had a significantly lower Kinaesthetics competence.
Conclusions The AdKinPal program can raise nurses' Kinaesthetics competence. Thereby, patients' autonomy and quality of life could be supported, and symptom management could be enhanced in a holistic manner. Furthermore, the AdKinPal program fosters nurses' self-efficacy in ADL support in end-of-life care. A strong sense of self-efficacy enhances professional well-being in many ways. Additionally, the nursing staff's musculoskeletal health can be promoted by enhancing their Kinaesthetics competence.